Classification of Korean forests: patterns along geographic and environmental gradients. Issue 1 (28th July 2014) - Černý, Tomáš; Kopecký, Martin; Petřík, Petr; Song, Jong‐Suk; Šrůtek, Miroslav; Valachovič, Milan; Altman, Jan; Doležal, Jiří; Bruelheide, Helge
Abstract Aim To describe the main vegetation types of the Korean zonal forests and explore their relationship with the main environmental and geographic gradients. Location Korean Peninsula. Methods A data set of 3847 relevés of zonal (semi)natural forest stands, together with environmental factors recorded in the field or derived from interpolated climatic data was collected. Using the hierarchical ISOPAM method, the relevés were classified into main forest types and their species composition, diversity and distribution were described. Their differentiation along main environmental gradients was analysed with classification and regression trees. Results Eleven vegetation types of forests were distinguished and assigned to five vegetation classes: Quercetea mongolicae (representing the core of the Korean temperate forests), Vaccinio‐Piceetea (subalpine coniferous forest), Fagetea crenatae (rare beech‐dominated forest included within a sub‐montane and sub‐oceanic type of oak‐dominated forest), Querco mongolicae‐Betuletea davuricae (sub‐continental drought‐ and fire‐tolerant forest, differentiated along elevational gradient) and Camellietea japonicae (oceanic evergreen forest). At a higher hierarchical level, these 11 vegetation types were grouped into three clusters, which most probably reflect different vegetation development in the Late Pleistocene and Holocene. Within the three major vegetation clusters, each forest type occupies a distinct environment. The forest types are especially well separated along elevational and temperature gradients. The distribution of individual forest types is joinly driven by total amount of incoming energy and thermal extremes, both affecting water supply to plant communities. Conclusions All distinguished vegetation types can be assigned to the recent syntaxonomic classification system. However, three main vegetation clusters do not correspond to traditionally distinguished syntaxonomic units. Nevertheless, the forest types within these clusters share common species with similar ecology and, especially, migration histories during the late glacial and post‐glacial periods. Therefore, we interpret these clusters as biogeographic patterns reflecting vegetation history rather than the current environmental conditions.